Heterostructured Co0.5Mn0.5Fe2O4-polyaniline nanofibers: highly efficient photocatalysis for photodegradation of methyl orange - Jung, Hong-Ryun; Kim, Kyung Nam; Lee, Wan-Jin (The Korean journal of chemical engineering, 2019)
1D hollow Co 0.5 Mn 0.5 Fe 2 O 4 -PANI nanofibers were synthesized through sequential processes of electrospinning, heat treatment in air, and chemical polymerization of polyaniline. The morphology and photocatalytic properties of heterostructured Co 0.5 Mn 0.5 Fe 2 O 4 -PANI as photocatalysts were investigated by SEM, TEM, XRD, TGA, and photocatalysis experiments of methyl orange under visible-light irradiation. The hollow Co 0.5 Mn 0.5 Fe 2 O 4 -PANI nanofibers showed a high photocatalytic degradation efficiency of 92% within 120 min and a kinetic constant of 115-times higher than hollow Co 0.5 Mn 0.5 Fe 2 O 4 nanofibers. These high photocatalytic properties are attributed to both unique 1D hollow nanofiber morphology with macroporous hollow core, PANI/Co 0.5 Mn 0.5 Fe 2 O 4 /PANI shell and the heterojunction structure composed of Co 0.5 Mn 0.5 Fe 2 O 4 and PANI. In addition, the outstanding magnetic properties of the hollow Co 0.5 Mn 0.5 Fe 2 O 4 -PANI nanofibers with its inherent spinel structure facilitate the recovery of the photocatalyst.